THE IMPACT OF SOME INDICATORS OF BANKING EFFICIENCY IN ACHIEVING FINANCIAL SAFETY - Saad Hamad Abdullah; Assistant Professor. Dr. Ibrahim Ali Kurdi (Scholars Digest Publishing, 2024)
The objective of this research is to showcase the impact of banking efficiency indicators on the attainment of financial stability within the selected banks, in comparison to the return on equity and return on assets indices. The research inquiry was prompted by the following question: Does the presence of banking efficiency indicators have a significant influence on the financial stability of the examined banks? To address this, both the null hypothesis and the alternative hypothesis were tested. The null hypothesis stated that there is no noteworthy correlation or effect between the banking efficiency indicators (return on equity, return on assets) and financial stability. Conversely, the alternative hypothesis posited that there is indeed a correlation and a significant effect between these indicators and financial safety. The study focused on private Iraqi commercial banks that are listed on the Iraq Stock Exchange. A sample of five banks was selected based on the availability of their financial data throughout the entire study period. The hypotheses were assessed using Excel's analytical description program and SPSS for statistical analysis. By examining the correlation between the study's variables, the research arrived at a number of findings, the most significant of which is that the banks included in the sample demonstrated a remarkable level of proficiency and competence in overseeing their operations and banking functions, as well as identifying areas of improvement and excellence. The study strongly advises decision makers to assess the bank's performance using metrics of banking efficiency and its contribution in determining the ideal blend to attain utmost effectiveness.
Keywords: return on equity index, return on assets index, capital adequacy index, liquidity index.